THE USAGE OF TABOOS AND EUPHEMISM IN EVERYDAY CONVERSATIONS (Western European Journal of Linguistics and Education, 2023)
The article explores the multifaceted aspects of taboo language and euphemisms within everyday English. It sheds light on how these linguistic tools are utilized, providing insight into their societal, cultural, and communicative implications. The research delves into various contexts where taboo language and euphemisms are employed, highlighting their evolution and impact on language use and social interactions.